Occurrence of Multidrug Resistant Escherichia coli in Raw Meat and Cloaca Swabs in Poultry Processed in Slaughter Slabs in Dar es Salaam, Tanzania - Fauster X. Mgaya; Mecky I. Matee; Amandus P. Muhairwa; Abubakar S. Hoza (MDPI AG, 2021)
This cross-sectional study was conducted between January and June 2020, in five large poultry slaughter slabs in Dar es Salaam, Tanzania. Purposive sampling was used to select broilers and spent layers, from which meat and cloaca swabs were collected to determine the occurrence of multidrug resistant (MDR) Escherichia coli. Identification of isolates was done using API 20E, and antimicrobial susceptibility testing was performed as per CLSI (2018) guidelines. EBSL (CTX-M, TEM, SHV) and plasmid mediated quinolone (qnrA, qnrB, qnrS and aac(6')-Ib-cr) were screened using PCR. Out of 384 samples, 212 (55.2%) were positive for E. coli, of which 147 (69.3%) were resistant to multiple drugs (MDR). Highest resistance was detected to tetracycline (91.9%), followed by sulfamethoxazole-trimethoprim (80.5%), ampicillin (70.9%), ciprofloxacin (40.2%) and 25% cefotaxime, gentamycin (10.8%) and imipenem (8.6%) (95% CI, p < 0.01). Out of the E. coli-positive samples, ten (10/212) (4.7%) were ESBL producing E. coli, of which CTX-M was detected in two isolates and quinolones resistant gene (qnrS) in eight, while TEM, SHV, qnrA, qnrB and aac(6')-lb-cr were not detected. The high level of resistance and multidrug resistance imply these antibiotics are ineffective, add unnecessary cost to poultry farmers and certainly facilitate emergence and spread of resistance.